OBSERVATIONS ON THE BIOLOGY OF CUTTLEFISH SEPIELLA INERMIS AT MANDAPAM - Unnithan, K Asokakumaran (Indian Journal of Fisheries, 2011)
Sepiella inermis was found to grow to a size of 50 mm at the end of firstyear and 80 mm of mantle length at the end of second year. The size at firstsexual maturity is 50 mm for males and 31 mm for females. Prawns were themain item of food of the species